Correlation between minimal changes in cardiac function, esophageal motility and heart rate variability in patients with the indeterminate form of Chagas Disease - Danielle Melo de Leopoldino (2011)
Chagas disease (CD) is currently the fourth most impacting disease in Latin America. Infected individuals are at continued risk of developing chronic cardiomyopathy―the main cause of morbidity and mortality. CD may also lead to intrinsic denervation of the enteric nervous system (ENS). Previous studies have described important changes in the autonomic nervous system, myocardium and digestive system. Indeterminate chronic Chagas disease (ICD) is asymptomatic and cannot be detected by simple tests such as electrocardiography, esophagography, contrast enema or chest radiography. However, minimal changes in cardiac and digestive functions have been reported for patients without clear clinical signs of cardiac or ENS denervation. We hypothesize these changes may be due to autonomic dysfunction. The purpose of this study was to evaluate esophageal motility and ventricular function and their correlation with heart rate variability (HRV) in subjects with ICD. Methods. Sixteen subjects with ICD and 8 healthy controls were submitted to electrocardiography for 30 min. with monitoring of HRV in the time and frequency domains, echocardiography with monitoring of cardiac function (systolic/diastolic) and six-channel perfusion esophageal manometry. Results. The systolic function (ventricular ejection fraction) was preserved in ICD patients and controls (66.1Â7.28 vs. 69.1Â6.36; p=0.35), but a significant difference was observed in tissue Doppler E‟ wave values (0.12Â0.02 vs. 0.14Â0.01; p=0.02). The average E wave deceleration time was longer for ICD patients but the difference did not reach statistical significance (200.81Â35.17 vs. 191.57Â36.08). As for the HRV time domain, the average NN50 (27.93Â33.97 vs. 138.75Â176.13; p=0.02), pNN50 (2.61Â3.47 vs. 11.66Â16.16; p=0.04) and geometric index (9757Â2787 vs. 13059Â2793; p=0.01) were significantly lower for patients with ICD. Although SDNN (50.18Â22.48 vs. 53.55Â12.61; p=0.70) and rMSSD (23.05Â13.78 vs. 32.32Â18.18; p=0.18) were lower for ICD subjects on the average, the difference was not significant. In the frequency domains (expressed in normalized units), HF-FFT (fast Fourier transformation) (29.40Â13.96 vs. 43.25Â12.95; p=0.03), HF-AR (autoregressive) (29.26Â14.7 vs. 43.71Â12.54; p=0.02), LF-FFT (70.59Â13.96 vs. 56.75Â12.54; p=0.03) and LF-AR (70.74Â14.75 vs. 56.28Â12.54; p=0.02) differed significantly between the groups, with ICD patients displaying lower average HF values and higher average LF values, whether by FFT or AR. The inferior sphincter relaxation time was longer for ICD patients (8.68Â2.95 vs. 5.73Â1.80; p=0.04). A significant correlation was observed between E‟ wave values and HF-FFT (rÂ=0.37; p=0.01), between E‟ wave values and HF-AR (rÂ=0.38; p=0.01), between sphincter relaxation time and HF-AR (rÂ=0,55; p=0.01) and between sphincter relaxation time and LF-AR (rÂ=0.39; p=0.05). Conclusion. HF values were significantly lower and LF values significantly higher in individuals with ICD than in normal controls, possibly due to predominantly sympathetic dysautonomia. E‟ wave values were significantly lower in ICD patients possibly due to minimal changes in diastolic function. In addition, the inferior sphincter relaxation time was significantly longer in subjects with ICD. Dysautonomia and functional changes of the left ventricle and esophagus may be dependent phenomena.